6x+18=3x-1

Simple and best practice solution for 6x+18=3x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+18=3x-1 equation:



6x+18=3x-1
We move all terms to the left:
6x+18-(3x-1)=0
We get rid of parentheses
6x-3x+1+18=0
We add all the numbers together, and all the variables
3x+19=0
We move all terms containing x to the left, all other terms to the right
3x=-19
x=-19/3
x=-6+1/3

See similar equations:

| -2x-5=-71 | | -24+3b=3(b-8) | | k+(-5)=-14 | | 18=-3x-(-3x+10) | | 4.9x=24.5 | | 2x^-14x+24=0 | | 63=9r | | 2(x-1)-8=7(x-7) | | 3.95+3+8.95b=47.65 | | -7x-7(3x-6)=10+4(-7x+8) | | (-6x+46)+(-9x+29)=180 | | 495=165+55m | | -8x+8=−8x+8 | | 20+(4x-6=6x | | 0=4+w/5 | | 5x+10=3x+2x-8 | | 5z=-8+6z | | x+5=(x–2)–(2x–7 | | -3(x+5+3x)-5(x+5+3x)=24 | | w-2=6.5 | | -354=6(8r-3) | | 3/4z+5=25 | | 2-(3x-3)=5x-3 | | 14-7(9v+3)=13v+41​ | | 7x-6=18-6x | | -2=-5x+24 | | 12x(4-3)=4(6x+4)-4 | | 6x-(3x+4)=4x-39 | | 1/2x-3/4=5/3 | | 5(2x+7)=-11+16 | | N/10n=5n+10 | | 3x-2+7x+4=4x+28 |

Equations solver categories